Medically assisted reproduction and birth outcomes: a within-family analysis using Finnish population registers. Issue 10177 (23rd March 2019) - Goisis, Alice; Remes, Hanna; Martikainen, Pekka; Klemetti, Reija; Myrskylä, Mikko
Summary: Background: Children born after medically assisted reproduction are at higher risk of adverse birth outcomes than are children conceived naturally. We aimed to establish the extent to which this excess risk should be attributed to harmful effects of treatment or to pre-existing parental characteristics that confound the association. Methods: We used data from Finnish administrative registers covering a 20% random sample of households with at least one child aged 0–14 years at the end of 2000 (n=65 723). We analysed birthweight, gestational age, risk of low birthweight, and risk of preterm birth among children conceived both by medically assisted reproduction and naturally. First, we estimated differences in birth outcomes by mode of conception in the general population, using standard multivariate methods that controlled for observed factors (eg, multiple birth, birth order, and parental sociodemographic characteristics). Second, we used a sibling-comparison approach that has not been used before in medically assisted reproduction research. We compared children conceived by medically assisted reproduction with siblings conceived naturally and, thus, controlled for all observed and unobserved factors shared by siblings. Findings: Between 1995 and 2000, 2776 (4%) children in our sample were conceived by medically assisted reproduction; 1245 children were included in the sibling comparison. Children conceived by medically assisted reproduction had worse outcomes than did those conceived naturally, for all outcomes, even after adjustments for observed child and parental characteristics—eg, difference in birthweight of −60 g (95% CI −86 to −34) and 2·15 percentage point (95% CI 1·07 to 3·24) increased risk of preterm delivery. In the sibling comparison, the gap in birth outcomes was attenuated, such that the relation between medically assisted reproduction and adverse birth outcomes was statistically and substantively weak for all outcomes—eg, difference in birthweight of −31 g (95% CI −85 to 22) and 1·56 percentage point (95% CI −1·26 to 4·38) increased risk of preterm delivery. Interpretation: Children conceived by medically assisted reproduction face an elevated risk of adverse birth outcomes. However, our results indicate that this increased risk is largely attributable to factors other than the medically assisted reproduction treatment itself. Funding: European Research Council, the Academy of Finland, and the Signe and Ane Gyllenberg Foundation.